Christian Democracy at the Local Level in the Post-Dictatorship Era: Political Practices and Clientele Relations in a Chilean Comuna - Pérez-Contreras, A (FAC LATINOAMERICANA CIENCIAS SOCIALES-FLACSO, ECUADOR, 2018)
This work analyses the interactions between the population of a Chilean comuna and two local authorities of the Christian Democrat Party: a former mayor and current municipal councillor. Through a diachronic analysis including in-depth interviews and political ethnography we analyse how concepts and practices around the exercise of politics are understood by these politicians and analyse ow they interact with the local population. We analyse how notions about politics, loyalty and the proper behaviour of an elected official are understood. Through the issues analysed we provoke the reader to rethink "clientelism" and its role in everyday life and in state building at the local level.